(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Human blood has always been in demand in health care facilities and most especially in disaster risk reduction management and the safe blood for transfusion is the blood donated by volunteer donors. The present paper inquires on the determinants of the intent to donate blood and the actual behavior of donating blood among volunteer student donors. The current inquiry employed the Theory of Planned Behavior in order to identify those attitudes (behavioral, cognitive and affective), significant or influential others as well as those conditions that influence the intent to and the actual behavior of donating blood among nonremunerated volunteers. A sample of 205 college students from a University campus that regularly holds blood donation provided the data through a questionnaire constructed by the researcher as guided by the constructs of the Theory of Planned Behavior. The researcher employed SPSS version 20 to establish the reliability indices of the whole instrument and its subscales as well as the convergence validity indices of the subscales. Structural equation modeling established fitness of the data for further analysis (x2 = 12.287, p > .05). Descriptive analysis generally indicated favorability of the respondents to volunteerism in blood donation, the mean of each construct being above the midpoint of the range of values. Societal Relative Advantage, Self-efficacy, Emotions and Personal; Control predicted the intent to donate blood by as much as 42%. Facilitating conditions, Societal relative Advantage, Personal Relative Advantage and Personal Control predicted the actual behavior of donating blood by as much as 55%. However, the intent to donate blood did not significantly load on the model that predicted the actual behavior to donate blood. Exploring these predictors and operationalizing them may provide professional involved in blood services the landscape that sustain volunteerism among current donors, the strategies in attracting potential donors to be volunteers and the marketing plan to increase the public’s support for this undertaking.